Fact checking: comparative analysis of the experience of Bulgaria, Britain and Kazakhstan - Tekenova Ә.М.; Tahan С.Ш. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The outbreak of the COVID-19 coronavirus infection, that has caused a worldwide uproar, the fight against false information and fact-checking becomes increasingly important today. Factchecking and Media literacy of journalists and their audiences has a special importance for the world media space. Therefore, the article determines the path to the solution of the problem, offering an expert interview with specialists from Bulgaria and the United Kingdom, as well as with the editor-inchief of the project of “Factcheck Kazakhstan” on fighting fake news and increasing media literacy